Extracellular vesicles secreted by Schistosoma mansoni contain protein vaccine candidates. Issue 1 (January 2016) - Sotillo, Javier; Pearson, Mark; Potriquet, Jeremy; Becker, Luke; Pickering, Darren; Mulvenna, Jason; Loukas, Alex
Graphical abstract: Highlights: First description of exosome-like extracellular vesicles (EVs) from Schistosoma mansoni adult worms. Schistosoma mansoni EVs purified by Optiprep density gradient yielded highly pure EV preparations. EV proteome possessed numerous known vaccine candidates, potential virulence factors and molecules implicated in feeding. These findings provide new avenues for the exploration of host–schistosome interactions and vaccine development. Abstract: Herein we show for the first time that Schistosoma mansoni adult worms secrete exosome-like extracellular vesicles ranging from 50 to 130 nm in size. Extracellular vesicles were collected from the excretory/secretory products of cultured adult flukes and purified by Optiprep density gradient, resulting in highly pure extracellular vesicle preparations as confirmed by transmission electron microscopy and Nanosight tracking analysis. Extracellular vesicle proteomic analysis showed numerous known vaccine candidates, potential virulence factors and molecules implicated in feeding. These findings provide new avenues for the exploration of host–schistosome interactions and offer a potential mechanism by which some vaccine antigens exert their protective efficacy.